Machinability of inconel 718 during turning: Cutting force model considering tool wear, influence on surface integrity - Toubhans, Bastien; Fromentin, Guillaume; Viprey, Fabien; Karaouni, Habib; Dorlin, Théo (Journal of materials processing technology, 2020)
[Display omitted] •Machinability of Inconel 718 is studied in finish turning conditions using carbide tools.•A mechanistic cutting force model is improved for round inserts.•A new local formulation is tested to take tool wear into account.•This original model is validated over a wide range of finishing parameters.•Residual stresses under the machined surface are studied depending on tool wear. Machining accuracy can be compromised by elastic workpiece deformation and subsurface residual stress introduction during cutting. In order to anticipate the impact of cutting forces and surface integrity evolutions on finished surface and its geometrical errors, it is necessary to better understand the influence of cutting conditions and tool wear. In this study, machinability of Inconel 718 using a round carbide tool in finish turning conditions is assessed. Cutting forces evolution during tool life are analysed and accompanied by advanced investigations of cutting phenomena. An original mechanistic cutting force model is developed, identified and tested. It includes the effect of tool wear over time in its local formulation. This model allows predicting cutting forces evolution along tool pass for a wide range of finishing cutting conditions. Furthermore, a thorough analysis of residual stress profiles at different tool wear levels is led. It features quantitative results for fresh and worn tools. A study on the influence of cutting parameters and tool wear on residual stress profiles in the machining affected zone is highlighted.